Paediatric BCOR‐associated sarcomas with a novel long spliced internal tandem duplication of BCOR exon 15 - Jian Yuan Goh; Chik Hong Kuick; Masahiro Sugiura; Sze Jet Aw; Manli Zhao; Hongfeng Tang; Sandini Gunaratne; Fucun Zhu; Lin Cai; Bin Tean Teh; Paul S Thorner; Kenneth Tou En Chang (Wiley, 2022)
Abstract Clear cell sarcoma of the kidney (CCSK) and primitive myxoid mesenchymal tumour of infancy (PMMTI) are paediatric sarcomas that most commonly harbour internal tandem duplications (ITDs) of exon 15 of the BCOR gene, in the range of 87-114 base pairs (bp). Some cases, instead, have BCOR‐CCNB3 or YWHAE‐NUTM2 gene fusions. About 10% of cases lack any of these genetic alterations when tested by standard methods. Two cases of CCSK and one PMMTI lacking the aforementioned mutations were analysed using Archer FusionPlex technology. Two related BCOR exon 15 RNA transcripts with ITDs of lengths 388 and 96 bp were detected in each case; only the 388 bp transcript was identified when genomic DNA was sequenced. In silico analysis of this transcript revealed acceptor and donor splice sites indicating that, at the RNA level, the 388‐bp transcript was likely spliced to form the 96‐bp transcript. The results were confirmed by Sanger sequencing using primers targeting the ITD breakpoint. This novel and unusually long ITD segment is difficult to identify by DNA sequencing using typical primer design strategies flanking entire duplicated segments because it exceeds the typical read lengths of most sequencing platforms as well as the usual fragment lengths obtained from formalin‐fixed paraffin‐embedded material. As diagnosis of CCSK and PMMTI may be challenging by morphology and immunohistochemistry alone, it is important to identify mutations in these cases. Knowledge of this novel BCOR ITD is important in relation to primer design for detection by sequencing, and using RNA versus DNA for sequencing.